Public health activities: Evaluation of community pharmacists’ attitude, practice, and barriers in a Nigerian southwestern state (2023)
The Nigerian health system continues to face double burden of communicable and non-communicable diseases. To meet the country’s health needs, the number of healthcare professionals participating in public health activities must be increased. The purpose of this study was to assess the attitudes, practices and barriers to rendering public health services among community pharmacists in a southwestern Nigerian state. We used a pretested self-administered questionnaire to collect data on 120 community pharmacists’ socio-demographic characteristics, practices, attitudes and barriers to providing public health services. Participating pharmacists must have at least one year of experience working in a community pharmacy. Data were summarised descriptively using IBM SPSS (version 23.0). Females’ respondents were (n = 69, 57.5%) and (n = 82, 68.3%) pharmacists had 1 year–5 years’ experience. Most (n = 116, 96.7%) of the respondents agreed that pharmacists should be involved in public health activities, and (n = 106, 88.3%) respondents disagreed that public health activities should be carried out only by doctors and nurses. Overall (n =89, 74.0%) of the respondents had positive attitude to public health activities (score ≥ 80%) and majority of the community pharmacists had been practicing public health activities. Insufficient time (n = 65, 54.2%) and lack of financial capital to implement changes (n = 84, 70.0%) were identified as prominent barriers that hindered community pharmacists from rendering public health services. Community pharmacists had positive attitude towards the practice of public health activities. However, further studies should emphasise on how to overcome barriers preventing their involvement in public health activities. Providing incentives for public health services rendered could increase community pharmacists’ involvement in public health activities.